Adaptation of the Fanfiction Comic “the Story of Kresna’s Birth” in to Webtoon Format - I Putu Egga Putra Adnyana; I Gusti Made Budiarta; Nyoman Sila (Jurnal Multidisiplin Sahombu, 2026)
Amidst the surge of numerous comics with contemporary plots and limitless story creations, it demands us to continuously adapt to the developments of the times in order to remain competitive in the creative world. One form of creativity is by combining creative elements from digital comics, such as webtoons, with famous traditional literary works that are rich in heroic elements, like the Mahabharata story. This study aims to: 1) describe the process of digitally creating "the story of Krishna's birth" in a Webtoon format, and 2) describe the results of digitally visualizing "the story of Krishna's birth" in a Webtoon format. In creating this work, the method used is idea exploration through D&D (Design and Development), where the idea exploration involves techniques for processing data into a design, which is then developed into a Webtoon comic work based on the story of the Birth of Krishna. Thus, it successfully concludes: 1) the process of creating "The Story of Krishna's Birth" in webtoon format has been described in detail. 2) In this visualization of Creation, it has successfully adapted the classic story into the vertical webtoon format. Keywords: Comic, Webtoon, Mahabharata, Fanfiction, The Story of Krishna's Birth